2023
DOI: 10.1186/s13568-023-01514-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome insights into the plant growth-promoting bacterium Saccharibacillus brassicae ATSA2T

Abstract: Endophytes can facilitate the improvement of plant growth and health in agriculturally important crops, yet their genomes and secondary metabolites remain largely unexplored. We previously isolated Saccharibacillus brassicae strain ATSA2T from surface-sterilized seeds of kimchi cabbage and represented a novel species of the genus Saccharibacillus. In this study, we evaluated the plant growth-promoting (PGP) effect of strain ATSA2T in kimchi cabbage, bok choy, and pepper plants grown in soils. We found a signif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 106 publications
1
4
0
Order By: Relevance
“…Nevertheless, other iron-siderophores involved in siderophore uptake were identified in the genomes, including a ferric uptake regulator ( perR ), and the iron ABC transporters afuABC and fbpABC . Furthermore, similar to our study, both ABC transporters in Saccharibacillus brassicae (Jiang et al 2023 ) and Virgibacillus halodenitrificans (Sharma et al 2023 ) were identified as siderophore transport systems. Therefore, we suggest that L. irui may be able to acquire iron and make it available to plants.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Nevertheless, other iron-siderophores involved in siderophore uptake were identified in the genomes, including a ferric uptake regulator ( perR ), and the iron ABC transporters afuABC and fbpABC . Furthermore, similar to our study, both ABC transporters in Saccharibacillus brassicae (Jiang et al 2023 ) and Virgibacillus halodenitrificans (Sharma et al 2023 ) were identified as siderophore transport systems. Therefore, we suggest that L. irui may be able to acquire iron and make it available to plants.…”
Section: Discussionsupporting
confidence: 89%
“…The four pst genes ( pstS , pstC , pstA , and pstB ) from the phosphate-specific transport (Pst), an important bacterial transport system for phosphate, were also present in all genomes analyzed. Previously, Yuan et al ( 2022 ) and Jiang et al ( 2023 ) had also reported the presence of pstABCS in the plant growth-promoting bacteria Paenibacillus peoriae and Saccharibacillus brassicae , respectively.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Current trends in agriculture are focused towards reducing the input of inorganic fertilizers and the use of PGP microbes to achieve sustainability. Mentioned hitherto, the world of PGP microbes remains unexplored as far as Choy Sum is concerned, although some reports have described such beneficial microbes and endophytic fungi in other Brassicaceae species [6][7][8][9][10]. Plant growth-promoting rhizobacteria (PGPR) colonize roots and enhance plant growth directly and indirectly [11,12].…”
Section: Introductionmentioning
confidence: 99%